Revascularization Results in the Interventional Management of Stroke II Trial - Tomsick, T.; Broderick, J.; Carrozella, J.; Khatri, P.; Hill, M.; Palesch, Y.; Khoury, J. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Our aim was to detail revascularization results, including impact on outcome and mortality, in the Interventional Management of Stroke (IMS) II trial.MATERIALS AND METHODS: IMS II was designed to obtain estimates of the efficacy and safety of reduced-dose intravenous recombinant tissue plasminogen activator (rtPA) followed by additional intra-arterial rtPA and low-energy sonography via the EKOS Primo Micro-Infusion Catheter at the occlusion in selected patients with ischemic stroke treated within 3 hours of onset. Revascularization outcomes were detailed and compared with modified Rankin Scale scores 0–2, mortality outcomes, and results from IMS I.RESULTS: Complete recanalization at 60 minutes occurred in 12 of 29 (41.4%) sonography microcatheter–treated occlusions. Complete recanalization was achieved at 2 hours or procedure end in 20/29 (68.9%) in the ultrasound catheter–treated group, and final thrombolysis in cerebral infarction (TICI) 2/3 reperfusion was achieved in 18/29 (62.0%) ultrasound-treated subjects. Fifteen-minute angiograms demonstrated some recanalization in 69/145 (46.7%) sonography microcatheter treatment intervals, compared with 39/111 (35.1%) in IMS I treatments in 23 subjects with reliable 15-minute angiograms (P = .046). Pooled IMS I-II data demonstrated that partial or complete recanalization occurred in 56/75 (74.6%) and good reperfusion (TICI 2/3) occurred in 46/75 (61.3%) of internal carotid artery T and M1 occlusions. Revascularization correlated with good outcome for TICI 2/3 reperfusion (P = .0004), TICI 2B/3 reperfusion (P = .0002), and arterial occlusive lesion 2/3 recanalization (P = .03).CONCLUSION: IMS II provides evidence that the EKOS Primo sonography microcatheter exhibits a trend toward improved recanalization of the occlusion compared with a standard microcatheter and again confirms the correlation between recanalization and reperfusion with good clinical outcome and reduced mortality.